2005
DOI: 10.4067/s0034-98872005001200006
|View full text |Cite
|
Sign up to set email alerts
|

Subdiagnóstico de delirium en adultos mayores hospitalizados

Abstract: Background: Delirium is a common underdiagnosed and undertreated problem in elderly inpatients (Rev Méd Chile 2005; 133: 1449-54).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
1
0
12
Order By: Relevance
“…Previous studies have found that delirium is overlooked in up to 68% of patients. (27) It has been reported that untreated delirium increases mortality rates up to three-fold, increases the chance of discharge to nursing home and increases long-term cognitive impairment by up to ten times. (5,12,28,29) As age is a major predisposing factor for delirium, failing to diagnose delirium will increase the economic burden of caring for elderly patients in Singapore's ageing population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that delirium is overlooked in up to 68% of patients. (27) It has been reported that untreated delirium increases mortality rates up to three-fold, increases the chance of discharge to nursing home and increases long-term cognitive impairment by up to ten times. (5,12,28,29) As age is a major predisposing factor for delirium, failing to diagnose delirium will increase the economic burden of caring for elderly patients in Singapore's ageing population.…”
Section: Discussionmentioning
confidence: 99%
“…En contraste con ellos, nuestro modelo incorpora a todos los pacientes, incluyendo aquellos que tengan deterioro cognitivo previo y aquellos que ingresen con delirium. Esto es una diferencia fundamental, considerando que hasta un tercio de los pacientes ingresan con delirium 2 y que existe un alto grado de subdiagnóstico de ambas condiciones, tanto del deterioro cognitivo como del delirium 4,30 . Esto le permite discriminar el nivel de riesgo de todos los pacientes en el momento de admisión, para así derivarlos a unidades con implementación de estrategias de prevención y manejo precoz de los casos de delirium, como recomienda la literatura 10 .…”
Section: Discussionunclassified
“…Diferentes estudios revelan que es una de las complicaciones intrahospitalarias más frecuentes, alcanzando una prevalencia de hasta 42% en pacientes hospitalizados por patologías médicas [2][3][4] . Uno de los factores que marcan la importancia del delirium es que afecta radicalmente el pro-nóstico del individuo.…”
unclassified
“…Puede ocurrir a cualquier edad, pero es mucho más frecuente en la población adulta mayor y, a la vez, subdiagnosticada (5,11,12) .…”
Section: Discussionunclassified
“…Estudios previos han determinado como factores de riesgo para desarrollar SCA a la demencia, polifarmacia o uso de psicofármacos (7)(8)(9)(10)(11)(12) .…”
Section: Introductionunclassified